Effect of melatonin in amelioration of piroxicam induced liver and renal oxidative stress in rats - H. S., Vivek; S. V., Rajendra; N., Harshitha; Y., Jyothi; A., Jothi (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Piroxicam, a nonsteroidal anti-inflammatory drug, induces oxidative stress affecting liver and kidney function. Melatonin, a potent antioxidant, may mitigate this damage through its free radical-scavenging and tissue-protective properties. Methods: The piroxicam-induced oxidative stress model was used to evaluate the amelioration effect of melatonin at two doses (10 mg/kg and 25 mg/kg BW). The changes in the physical, physiological and biochemical characteristics in the serum, liver and renal tissue oxidative stress markers, the histopathological changes and insilico docking of melatonin with various oxidative stress marker were also studied. Results: The blood serum and tissue stress markers in the rats receiving piroxicam was considerably higher than those in the normal control (p<0.05). Pre-treatment with melatonin at doses of 10 mg/kg and 25 mg/kg resulted in a substantial amelioration in tissue oxidative stress as compared to the control group. Other than lipid peroxidation, which exhibited a significant (p<0.05) plunge when compared to the piroxicam treated group, the serum liver and renal comprehensive metabolic panel profile was significantly reduced. In the pre-treatment group, the level of total protein contents likewise increased. Further it is confirmed from the histological studies that the pre-treatment of melatonin group’s liver and kidney show less tissue damage than the piroxicam-induced group, and the histo-architectural of hepato-renal cells gradually recovered and in silico docking study of melatonin with oxidative stress maker shown potential interaction with high binding energy. Conclusions: It can be concluded that pretreatment of melatonin is effective against piroxicam- induced liver and renal oxidative stress in the Wister rats.